A systematic review and narrative synthesis of fathers' (including migrant fathers') experiences of pregnancy and childbirth - Andy Mprah; Melanie Haith-Cooper; Eva Duda-Mikulin; Fiona Meddings (BMC, 2023)
Abstract Objective The purpose of this review was to consider factors that influence the experiences of pregnancy and childbirth by fathers including migrant fathers. Method A systematic review and narrative synthesis were conducted as per the PRISMA guidelines. The spider tool was used to build a search strategy which was used to conduct literature search in eight identified electronic databases: ASSIA, CINAHL, EMBASE, MEDLINE, PsycINFO, PUBMED, Sage and Scopus. Grey literature was searched through the King's Fund Library database, Ethos, The North Grey Literature Collection, Social Care Online and other charity websites such as the Refugee Council and Joseph Rowntree Foundation. The search was conducted across all the databases in the week commencing January 7, 2019, and restricted to studies published in the English language. Results The search across all the eight electronic databases identified 2564 records, 13 records through grey literature databases/websites and an additional 23 records identified through hand-searching/forward citation. The number of records after duplicates were removed was 2229. Record screening based on titles and abstracts identified 69 records for full text screening. Dual screening of these full text records identified 12 full records from 12 separate studies, eight of which were qualitative studies, three of which were quantitative studies and one mixed method study. Findings This review has revealed three main themes: influence of society and health professionals; adjustment to a new life of fatherhood; and involvement in maternity care. However, the literature has focused on non-migrant father's experiences of pregnancy and childbirth, with little attention paid to fathers who may be migrants. Key conclusion and implications for practice This review has exposed a dearth of research on migrant fathers' experiences of pregnancy and childbirth in an era of increasing globalisation and migration between countries. Midwives and other health professionals should be alert to the needs of any father when providing maternity care. More research is needed which considers experiences of migrants and how choosing to move to a new country or being forced to move could influence migrant father's experiences and therefore their needs.